ChemInform Abstract: Nickel(II) Uranium(IV) Trisulfide. Issue 16 (22nd April 2014) - Ward, Matthew D.; Ibers, James A.
Abstract Black prisms of NiUS3 and platelets of NiU8S17 as a side product are obtained from the reaction of Ni, U, S, and GeI2 in a CsCl flux (evacuated silica tube, 1073 K, 96 h).